A Microstructural Study of Load Distribution in Cartilage: A Comparison of Stress Relaxation versus Creep Loading - Ashvin Thambyah; V. M. van Heeswijk; C. C. van Donkelaar; Neil Broom (Advances in Materials Science and Engineering)
The compressive response of articular cartilage has been extensively investigated and most studies have focussed largely on the directly loaded matrix. However, especially in relation to the tissue microstructure, less is known about load distribution mechanisms operating outside the directly loaded region. We have addressed this issue by using channel indentation and DIC microscopy techniques that provide visualisation of the matrix microstructural response across the regions of both direct and nondirect loading. We hypothesise that, by comparing the microstructural response following stress relaxation and creep compression, new insights can be revealed concerning the complex mechanisms of load bearing. Our results indicate that, with stress relaxation, the initial mode of stress decay appears to primarily involve relaxation of the surface layer. In the creep loading protocol, the main mode of stress release is a lateral distribution of load via the mid matrix. While these two modes of stress redistribution have a complex relationship with the zonally differentiated tissue microstructure and the depth of strain, four mechanostructural mechanisms are proposed to describe succinctly the load responses observed.